Women's Empowerment and HIV Prevention in Rural Malawi. Issue 3 (2nd July 2016) - Gerritzen, Berit
ABSTRACT: This study examines the impact of women's empowerment on attitudes toward HIV prevention using the Malawi Diffusion and Ideational Change Project (MDICP), a panel dataset of over 1, 200 married women in rural Malawi from 1998 to 2008. Results indicate that an increase in women's bargaining power promotes adequate HIV prevention strategies, namely condom use within marriage and HIV-related spousal communication. Own income, language skills, and awareness of options outside marriage also play an important role. By estimating a constant for each individual in the sample, the analysis controls for the impact individual-specific, nonmeasurable characteristics have on attitudes toward prevention. It captures the impact of HIV campaigns and increases in HIV prevalence over time on prevention behavior by using (regional) time trends. The findings are highly comparable across different econometric specifications and suggest substantial gains from placing greater emphasis on women's empowerment to effectively combat the spread of HIV, particularly in developing countries.